-2+2n=2(6n+4)

Simple and best practice solution for -2+2n=2(6n+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+2n=2(6n+4) equation:


-2+2n=2(6n+4)

We simplify the equation to the form, which is simple to understand
-2+2n=2(6n+4)

Reorder the terms in parentheses
-2+2n=+(+12n+8)

Remove unnecessary parentheses
-2+2n=+12n+8

We move all terms containing n to the left and all other terms to the right.
+2n-12n=+8+2

We simplify left and right side of the equation.
-10n=+10

We divide both sides of the equation by -10 to get n.
n=-1

See similar equations:

| 3m=8m-110 | | -x-10=-20 | | 158-4x=23x+20 | | 5x+5=25-5x | | 28-8a=-4(8a+5) | | 7x^5*6x^5*13x+26=8 | | 13=-24 | | x+7=x-5 | | 6+2m=6(m+3) | | -2x^3+2x^2+12x=0 | | 4x^3*3x^2*2x+5=0 | | 2-y=2 | | 5*x=3 | | 17x-5=5+12x | | 49s^2-9= | | 0.8x+0.3=9 | | 7.4p-5.3-9.2p=-2.6 | | 9t=-36 | | 15a^2+26a-21=0 | | -x^2+2x+48=0 | | 3x^2=6x-7 | | 0.25x+0.375=0.875 | | 4m-1=5 | | 3p^2+22p-16=0 | | -1.6(x-18)+1.3(x+3)=x+34 | | -x^2+12x+28=0 | | -1.6(x-18)+0.5(x+3)=x-8 | | 11x+8=4x-27 | | x+3/2*8=x/8 | | 4+3a=4(a+2) | | 5b^2-22b+8=0 | | 4z^2+12z-az-3a= |

Equations solver categories